Modal adjuncts in the short story 'Grace', by Joyce, and in two of its translations into Brazilian Portuguese - Roberta Rego Rodrigues (Gragoatá, 2019)
Modal adjuncts belong to interpersonal metafunction (HALLIDAY, 1994). They can point to the narrator’s and the characters’ evaluation in literary texts. This paper aims to delve into these categories in the short story Grace (JOYCE, 2001) and in two of its interlingual reinstantiations into Brazilian Portuguese, one by José Roberto O’Shea (JOYCE, 2012), and the other one by Guilherme da Silva Braga (JOYCE, 2013). Modal adjuncts of the short stories were annotated by using CROSF (FEITOSA, 2006), and quantified on WordSmith Tools (version 6.0). The results point out that the source text has more modal adjuncts if compared to the translations. In addition, they show that mood adjuncts are more frequent than comment adjuncts in the corpus. It can be noticed that the translators use their translational creativity when they propose alternative translations to modal adjuncts.